2019
DOI: 10.15761/bgg.1000144
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between human genetic factors and Plasmodium falciparum genetic diversity of msp1, msp2 and glurp in a malaria endemic area of Burkina Faso

Abstract: Human genetic factors mechanisms are known to protect against malaria. However, the mechanism underlying the influence of human genetic variation on Plasmodium falciparum (P.falciparum) genetic diversity is still a research purpose. The aim of this study is to assess the effect of haemoglobin variants and Glucose-6-Phosphate-Dehydrogenase (G6PD) variation on the P. falciparum merozoite surface protein (msp1, msp2), and the glutamate rich protein (glurp) genetic diversity in children living in Burkina Faso (BF)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 20 publications
0
1
0
Order By: Relevance
“… 13 On the other hand, they are different from previous studies in Africa. Indeed, the Soulama’s studies in 2009 9 and Badoum 14 in 2019 in Burkina Faso and Hounto’s in Benin in 2013 15 reported that the K1 and FC27 allelic families were the most predominant one for msp-1 for msp-2 respectively. The predominance of RO33 and 3D7 alleles in our study could be explained by the effect of IPT/SP in favour of an increase in the “biological fitness” of these parasitic clones.…”
Section: Discussionmentioning
confidence: 98%
“… 13 On the other hand, they are different from previous studies in Africa. Indeed, the Soulama’s studies in 2009 9 and Badoum 14 in 2019 in Burkina Faso and Hounto’s in Benin in 2013 15 reported that the K1 and FC27 allelic families were the most predominant one for msp-1 for msp-2 respectively. The predominance of RO33 and 3D7 alleles in our study could be explained by the effect of IPT/SP in favour of an increase in the “biological fitness” of these parasitic clones.…”
Section: Discussionmentioning
confidence: 98%